2014
DOI: 10.1024/0301-1526/a000360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apoptosis in varicose vein disease complicated by superficial vein thrombosis

Abstract: The vein wall in SVT shows increased pro-apoptotic activity compared to uncomplicated disease and normal veins. Whether increased vein wall cell apoptosis is a causative factor for SVT in varicose veins disease or a repairing mechanism of the thrombosis itself needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Ducasse et al 28 have also documented that the process of programmed cell death is inhibited in varicose veins and suggested that the parietal cells in varicose veins live longer and become dysfunctional, which may lead to weakening or dilatation of the venous wall. Others have shown increased vein wall apoptosis in thrombophlebitic saphenous and varicose veins, and associated increased vein wall apoptosis with venous hypertension, 32,47 which are opposed to the results of the current study. We think that the differences in results involve disease severity, diseased category, and the part of vein taken etc.…”
Section: Discussioncontrasting
confidence: 99%
“…Ducasse et al 28 have also documented that the process of programmed cell death is inhibited in varicose veins and suggested that the parietal cells in varicose veins live longer and become dysfunctional, which may lead to weakening or dilatation of the venous wall. Others have shown increased vein wall apoptosis in thrombophlebitic saphenous and varicose veins, and associated increased vein wall apoptosis with venous hypertension, 32,47 which are opposed to the results of the current study. We think that the differences in results involve disease severity, diseased category, and the part of vein taken etc.…”
Section: Discussioncontrasting
confidence: 99%
“…59 Moreover, a histological study in human superficial vein segments found higher apoptosis activities in those containing thrombus. 60 The diverse pathways involved in cellular senescence converge on p53, a transcription factor controlling cell cycle, growth arrest, and apoptosis. 10,61 However, very little is known regarding p53 and the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown increased vein wall apoptosis in thrombophlebitic saphenous veins and varicose veins and associate it with venous hypertension. 13,14 However, our work state is the opposite. We think that the differences in results involve diseased severity and the part of vein taken etc.…”
Section: Discussionmentioning
confidence: 70%
“…12 (morphological, ultrastructural, cell proliferation and TUNEL method analysis were performed), and Filis et al. 13,14 (the expression of Bax, p53, caspase 3, Bcl-2, Bcl-6, Bcl-xs, Bcl-xl and Ki-67 were detected), while Ascher et al. 9,15 (apoptosis was detected by TUNEL assay; expression of bcl-2 and cyclin D1 was noted by standard immunohistochemical techniques) concluded that down-regulation of apoptosis occurred in primary varicose veins.…”
Section: Introductionmentioning
confidence: 99%